HAUTEAS: DISINGKIRKAN ATAU DILESTARIKAN? - Yetva Softiming Letsoin; Agustinus Opat; Oktovianus Robertus Baunsele (Program Studi Filsafat Universitas Katolik Widya Mandira Kupang, 2022)
In this search, our focus is on the meaning and significance of Hauteas and the Church's response to it. From these two things we try to trace the encounter of the Catholic faith with Hauteas itself. The methodology used is a qualitative method with interview techniques and library analysis in the form of text analysis through critical reading that listens to the understanding and understanding of Hauteas and the Catholic Church's view on Culture. The author argues that we cannot take the extreme choice that the Hauteas be removed, or the Hauteas preserved. We only need to come to a critical reflection that, the meeting point between the teachings of the Church and the Hauteas is actually in the communal and ecological values behind the Hauteas. With Hauteas people can increase the fellowship and spirit of brotherhood. In addition, people can limit themselves to illegal logging. Hauteas keeps the cultural traces in it. This includes religious values that help us not to be greedy in treating nature. But on the other hand, we cannot also accept the practice of offerings in Hauteas which can harm others because of the evil intentions of the practice.